Stakeholders’ Perception Toward Resource Mobilization in Rupandehi - Nepal, Pramshu (Butwal Campus Journal, 2020)
This paper analyzes the perception of the stakeholders toward resource mobilization in Rupandehi district. Using the questionnaire survey on purposive sample of 80 respondents representing government employees, former officials of LBs, representatives from civil societies and NGOs, and experts on fiscal decentralization and local development, the study reports that many of the stakeholders are not satisfied with the current local resources mobilization practices of Rupandehi district. As the study indicates, there is resource gap in local level to meet the aspiration and demand of people. Thus, the study results show that, in order to mobilize effectively the local resources in development activities, the capacity of local bodies needs to be enhanced.